2017
DOI: 10.1080/24750263.2017.1403656
|View full text |Cite
|
Sign up to set email alerts
|

Age, sex and seasonal variation in the shape and size of erythrocytes of the alpine accentor,Prunella collaris(Passeriformes: Prunellidae)

Abstract: To cite this article: M. Janiga, M. Haas & M. Kufelová (2017) Age, sex and seasonal variation in the shape and size of erythrocytes of the alpine accentor, Prunellacollaris AbstractThe aim of our study was to analyse red blood cells from the high-altitude avian species alpine accentor (Prunella collaris). We caught 79 alpine accentors in the High Tatra Mountains (the West Carpathians, Slovakia) from 2001 to 2008. Blood samples were collected from the vena ulnaris cutanea. The cells and nuclei of juveniles tend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 42 publications
2
14
0
Order By: Relevance
“…they have a lower metabolic rate per volume unit, due to their relatively smaller membrane surface to cell volume, which should determine the cell metabolic rate (Starostová et al 2013). However, in our research, we found the largest erythrocytes occurred during the molting period, and a similar trend was observed in erythrocytes of alpine accentors in winter (Janiga et al 2017). A possible explanation is given by an interpretation of a study from Buttemer et al (2019), wherein cells remain less active despite increased metabolism of an organism such as during the molt period.…”
Section: Changes In the Shape And Size Of Erythrocytes Before During And After The Molt In Alpine Accentorssupporting
confidence: 84%
See 2 more Smart Citations
“…they have a lower metabolic rate per volume unit, due to their relatively smaller membrane surface to cell volume, which should determine the cell metabolic rate (Starostová et al 2013). However, in our research, we found the largest erythrocytes occurred during the molting period, and a similar trend was observed in erythrocytes of alpine accentors in winter (Janiga et al 2017). A possible explanation is given by an interpretation of a study from Buttemer et al (2019), wherein cells remain less active despite increased metabolism of an organism such as during the molt period.…”
Section: Changes In the Shape And Size Of Erythrocytes Before During And After The Molt In Alpine Accentorssupporting
confidence: 84%
“…Our previous study (Janiga et al 2017) showed a trend whereby the adult birds have the largest cells in the winter and the smallest in the summer when they remain at higher elevations during nesting and weather conditions are stable. As the mean or the variance of temperature increases, smaller cells can be efficient in the increased metabolism, especially for oxygen supply (Czarnoleski et al 2013(Czarnoleski et al , 2015.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Finally, erythrocyte shape can also vary, being rounder (smaller length to width ratio) or elongated (greater length to width ratio). Erythrocyte shape is poorly studied, but is known to vary plastically within‐species, for example, elongated erythrocytes were reported in alpine accentors breeding at high altitudes (Haas & Janiga, 2020; Janiga et al, 2017), whereas across bird species, erythrocytes were more elongated at higher altitudes and for species migrating long distances (Soulsbury et al, 2022). In contrast, cell shape (PCA of cell shape components) also varies extensively in teleosts, but did not vary with habitat or body size (Martins et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…One study on alpine accentors Prunella collaris , found that the red blood cells and nuclei of juveniles were longer and wider in chicks than adults (all birds older than one year), and that males tended to have elongated cells. Cells were also shown to have significant seasonal differences (Janiga et al 2017). Another study on Japanese quails Coturnix coturnix japonica found a significant difference in erythrocyte size in chicks < 1 week old and those 3 and 5 weeks old, with the youngest being the longest, although the opposite was found when they compared reticulocytes (Tadjalli et al 2003).…”
Section: Introductionmentioning
confidence: 99%